Numerical Simulation on Thermoelectric Cooling of Core Power Devices in Air Conditioning - Jiang Wang; Kai Hu; Kechen Tang; Yubing Xing; Yani Xiao; Yutian Liu; Yonggao Yan; Dongwang Yang (Applied Sciences, 2023)
Air conditioning has become a necessity in people’s daily life. The performance of the compressor determines the energy efficiency ratio of this electrical equipment, but the heat generated during the operation of its internal core power components will greatly limit its performance release, so it is urgent to carry out research on the heat dissipation of power devices. In this work, we explore the application of thermoelectric coolers (TECs) in the field of power device heat dissipation through finite element simulation. First, we geometrically modeled the structure and typical operating conditions of core power devices in air conditioners. We compared the temperature fields in air-cooling and TEC active cooling modes for high-power-consumption power devices in a 319 K operating environment. The simulation results show that in the single air-cooling mode, the maximum temperature of the 173.8 W power device reached 394.4 K, and the average temperature reached 373.9 K, which exceeds its rated operating temperature of 368.1 K. However, the maximum and average temperature of the power device dropped to 331.8 K and 326.5 K, respectively, at an operating current of 7.5 A after adding TECs, which indicates that TEC active cooling has a significant effect on the temperature control of the power device. Furthermore, we studied the effect of the TEC working current on the temperature control effect of power devices to better understand the reliability of the TECs. The results show that TECs have a minimum working current of 5 A, which means it has no significant cooling effect when the working current is less than 5 A, and when increasing the current to 10 A, the average temperature of the power device can be reduced to 292.9 K. This study provides a meaningful exploration of the application of TECs in chip temperature control and heat dissipation, providing a new solution for chip thermal management and accurate temperature control.